Preparation and X-ray Structures of 3-[Bis(trifluoroacetoxy)iodo]benzoic Acid and 3-[Hydroxy(tosyloxy)iodo]benzoic Acid: New Recyclable Hypervalent Iodine Reagents - Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Funk Т. V.; Chi Ki-Whan; Cha Eun-Hye; Kim Ghyung Hwa; Kirschning А.; Zhdankin V. V. Viktor Vladimirovich (2008, 2008)
Title screen